HOW IMPORTANT ROLE THE VOCABULARY PLAYS IN READING COMPREHENSION AMONG LANGUAGE LEARNERS - Gulkhayo Toshkhujaeva (Scholar Express Journal, 2022)
In first language (L1) contexts, the importance of vocabulary knowledge for reading comprehension has long been acknowledged, and it also seems to be true in second language (L2) contexts. However, little is known about how students' vocabulary size could affect their reading comprehension in connection to a sociocultural environment like Singapore, where English is listed as an L1 in the school curriculum but the majority of students still study it as an L2. This study was conducted to examine the impact of vocabulary in reading comprehension since vocabulary is frequently mentioned by students and instructors as the major reading challenge. In this study, 37 fourth-year secondary students from a Singapore neighborhood school took part. According to the findings, pupils' reading comprehension and vocabulary knowledge at the 2,000- and 3,000-word levels were connected. Only the short-answer questions produced a significant association, not the summary. Additionally highlighted are the pedagogical implications and suggestions for more study
Keywords: Reading comprehension; vocabulary knowledge; L1; reading materials